Серия переломов, подвергнутых лечению в Медико-механическом интституте за 1915 г. (ІV серия историй болезни) - Вегнер К.Ф.; Vegner K.F. (Мирный труд, 1915)
Описи історій хвороб пацієнтів Медико-механічного інституту

Descriptions of patient histories of the Medical-Mechanical Institute
A series of fractures treated at the Medico-Mechanical Institute in 1915 (IV series of case histories)